Clifford's First Christmas - Bridwell, Norman (New York Scholastic, 2007)
Clifford, a small red puppy, helps Emily Elizabeth decorate the Christmas tree, wrap presents, and enjoy Christmas day, in a book in which the cover features a see-through plastic ornament filled with a clear liquid and glitter.
Include Color Illustrations
Keywords: Clifford (Fictitious character : Bridwell) -- Christmas stories